2020
DOI: 10.3390/app10113907
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acids from Ganoderma lucidum Spores: Extraction, Identification and Quantification

Abstract: Ganoderma lucidum is a rich and promising source of bioactive compounds capable of positively influencing the human health. For this reason, G. lucidum is the target of vigorous investigational activities, focusing on the extraction of substances with potential biomedical applications, as well as on the improvement of analytical methodologies for their screening. In the present study, three different extraction processes (i.e., extraction with n-hexane, in Soxhlet apparatus with n-hexane and reflux with chloro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…From the calibration plots, the intercept and slope were obtained together with the corresponding standard deviations ( and ), calculated from the calibration data according to standard statistical procedures [ 32 ]. The standard deviation of the intercept, , was then used to calculate the method detection limit (LOD) according to the formula: ; and the quantification limit (LOQ) according to the formula: [ 33 , 34 ]. LOD and LOQ for PR170 were, respectively, 0.08 and 0.26 mg/L.…”
Section: Methodsmentioning
confidence: 99%
“…From the calibration plots, the intercept and slope were obtained together with the corresponding standard deviations ( and ), calculated from the calibration data according to standard statistical procedures [ 32 ]. The standard deviation of the intercept, , was then used to calculate the method detection limit (LOD) according to the formula: ; and the quantification limit (LOQ) according to the formula: [ 33 , 34 ]. LOD and LOQ for PR170 were, respectively, 0.08 and 0.26 mg/L.…”
Section: Methodsmentioning
confidence: 99%
“…The standard deviation of the intercept, , is used to calculate the method detection limit (LOD), according to the formula: LOD = ; and the quantification limit (LOQ), according to the formula: LOQ = [ 43 ].…”
Section: Methodsmentioning
confidence: 99%
“…velutipes, Lactarius salmonicolor, Pleurotus ostreatus, Polyporus squamosus, and Russula anthracina ) in from Anatolia where all selected species were reported to have cis -linoleic acid contributing to the highest portion in the fatty acid composition, which varied from 22.39 % to 65.29 % [ 18 ]. Majority of the literatures reveal that PUFAs including linoleic acid, α-linolenic acid, γ-linolenic acid, were the major fatty acids in being extracted from mushroom biomass, with linoleic acid being the most abundant PUFA and this evidence suggested that linoleic acid plays a crucial role in mushroom metabolism, in which the level of fatty acid will be affected based on the growth conditions, substrate, and other environmental factors [ [16] , [17] , [18] , [20] , [21] , [22] , [23] , [24] ].…”
Section: Types Of Fatty Acids From Mushroom Biomassmentioning
confidence: 99%
“…According to the findings demonstrated by Barros, Baptista [ 17 ], the percentages of oleic acid were higher than linoleic acid in Lactarius deliciosus , Sarcodon imbricatus , and Tricholoma portentosum , with the oleic acid to linoleic acid percentage ratio (%: %) of 41.26 : 17.06, 45.06 : 35.38, and 58.36 : 30.88, respectively [ 17 ]. Another study from Italy revealed that oleic acid was the predominant species of fatty acid in the fatty acid composition of Ganoderma lucidum with a remarkably high percentage of 60.1 %–68.4 %, obtained by performing different extraction techniques [ 22 ]. It had been observed that oleic acid was the main fatty acid with the greatest percentage in the biomass of Russula anthracina (52.11 %) in the fatty acid composition analysis [ 18 ].…”
Section: Types Of Fatty Acids From Mushroom Biomassmentioning
confidence: 99%
See 1 more Smart Citation